Evaluation of Holdaway Soft Tissue Analysis for Iraqi Adults with Class I Normal Occlusion - Manar Y Abdul-Qadir; Alaa' D Al-Dawoody; Ne'am F Agha (University of Mosul, College of Dentistry, 2010)
Aims: To establish a cephalometric standard for sagittal jaw relationships for Iraqi adolescents in Mosul city by using three linear measurements, also to compare &correlated the three methods. Materials and Methods: Lateral cephalometric radiograph were taken for 120 adolescents (52 boys and 68 girls). The age range was 12-15 years with a mean of 13.4 years. Wits appraisal (Ao-Bo), App-Bpp (distance between points A&B projected to the palatal plane), and AF-BF(distance between points A and B pro-jected to the Frankfort Horizontal plane) were measured. Results: Significant differences were found between boys and girls for Ao-Bo, and App-Bpp measurements. No significant difference was ob-served for AF-BF between girls and boys. Conclusions: Among the three measurements taken, the AF-BF distance appeared to be the most dependable one followed by App-Bpp distance.